2012
DOI: 10.2217/pme.12.80
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Direct-to-Consumer Genomic Information into Patient Care: Attitudes and Experiences of Primary Care Physicians

Abstract: Aim Despite predictions of increased clinical applications, little is known about primary care providers’ (PCPs’) readiness to apply genomics to patient care. The aim was to assess PCPs’ current experience with genetic testing, their assessment of the understandability and clinical utility of information in sample direct-to-consumer reports for genomic assessment of disease risk and warfarin dosing and attitudes toward genomic medicine. Materials & methods A web-based survey of PCPs who are members of Knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 45 publications
4
64
1
2
Order By: Relevance
“…Previous researches have demonstrated knowledge gap, good attitude and low practice towards PG among current Doctors and Pharmacists (Yau et al, 2015;Bakhouche and Slanař, 2012;Benzeroual et al, 2012;Bernhardt et al, 2012;Bonter et al, 2011;Stanek et al, 2012;Johansen Taber and Press, 2014;Yau et al, 2015b); Moreover, study conducted in Ukraine among Pharmacy students revealed similar results (Filiptsova et al, 2015). However, study carried out in Malaysia, have discovered that current healthcare practitioners have good knowledge, attitude and consider PG to be a relevant field of clinical practice, but with low adoption (Bannur et al, 2014), and other studies have demonstrated healthcare students agree that PG is critical to patient care (Drozda et al, 2013;Gurwitz et al, 2005;McCullough et al, 2011;Moen and Lamba, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches have demonstrated knowledge gap, good attitude and low practice towards PG among current Doctors and Pharmacists (Yau et al, 2015;Bakhouche and Slanař, 2012;Benzeroual et al, 2012;Bernhardt et al, 2012;Bonter et al, 2011;Stanek et al, 2012;Johansen Taber and Press, 2014;Yau et al, 2015b); Moreover, study conducted in Ukraine among Pharmacy students revealed similar results (Filiptsova et al, 2015). However, study carried out in Malaysia, have discovered that current healthcare practitioners have good knowledge, attitude and consider PG to be a relevant field of clinical practice, but with low adoption (Bannur et al, 2014), and other studies have demonstrated healthcare students agree that PG is critical to patient care (Drozda et al, 2013;Gurwitz et al, 2005;McCullough et al, 2011;Moen and Lamba, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lot of developments have been made in the field of PG over six decades, and its promising roles in ADRs, drugs safety and efficacy. However, the practical application of PG has been below expectation (Bannur et al, 2014;de Denus et al, 2013). In general, PG is not yet seen as an essential tool in drug safety, therefore not an important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this process, PGx testing can be completed at home by the patient, but still involves supervision from the ordering healthcare provider. This is distinct from direct-toconsumer testing where a healthcare provider does not need to be involved in the process [1,[21][22][23]. Increased access to health information on the internet, demand for personal healthcare autonomy and lower test costs have likely increased the demand for these servicesas healthcare has become more consumer-driven [22].…”
Section: Introductionmentioning
confidence: 99%
“…This is distinct from direct-toconsumer testing where a healthcare provider does not need to be involved in the process [1,[21][22][23]. Increased access to health information on the internet, demand for personal healthcare autonomy and lower test costs have likely increased the demand for these servicesas healthcare has become more consumer-driven [22]. However, controversy remains regarding potential risks and benefits of consumer-driven access to genomic information [1,21,23].…”
Section: Introductionmentioning
confidence: 99%